Desafios das licenciaturas em educação do campo no estado do Paraná : lutas e conquistas das lideranças camponesas (2007-2020) - Rossetto, Edimar Rodrigo (2020)
Nowadays it is essential to link the rural school with the movements for the struggle for land in Brazil. The socio-territorial movements of the countryside, based on local, regional articulations, with national and international scope stand out for guaranteeing public policies that reaffirm rights, such as, for example, the guarantee of public and free education to peasant communities. Meanwhile, this movement takes shape and the popular project of Rural Education is born. Based on the struggles for the construction of public policies that, although ensured by legislation, are not always concretely implemented.This is the case of the courses of Rural Education Degree. The bias of this course foresees in its objectives the formation of a “new educator from the countryside”, aware of the peasant reality and, above all, an important subject in the continuity of the maintenance of community life, collective work, traditions and beliefs, in the heterogeneous group existing in the Brazilian field. In this sense, the research has as spatial cut, the state of Paraná where the researched universities are located, namely, State University of the West of Paraná - UNIOESTE, Cascavel campus, located in the western region, the State University of the Midwest - UNICENTRO, Guarapuava campus, located in the south-central region of the State, the Federal Technological University of Paraná - UTFPR, Dois Vizinhos campus, located in the southwest region and the Federal University of Fronteira Sul - UFFS, Laranjeiras do Sul campus, located in the southern region, all, in the geomorphological unit of the third plateau of Paraná. The choices of these institutions are justified because they are the only public universities in the region to offer the Degree Course in Rural Education in the State of Paraná. The main objective of this thesis is to understand the role of the leaders who are at the head of the courses, in understanding their functionality, the fruits of the struggle for an education consistent with the interests of the peasant communities that each institution covers. It is about presenting new possibilities and new limits in the understanding of the context of building a course that meets the demands of local communities in the education of rural educators based on the work / action of each leadership, of each subject involved in the process in order to enable quality training for educators, preserving community life in the countryside, the culture and way of life of communities. In terms of methodology, the theoretical framework was carried out through works, theses, dissertations and monographs on the subject in question. The empirical work consisted of data collection in the research fields, that is, in the four universities studied, with analysis of course documents, in addition to analyzes of public policies that served as a legal apparatus for the institutionalization of curricular proposals and the Rural Education in Brazil. In this sense, the design comprises bibliographic, documentary and case study research, characterized as having an explanatory level, by grouping theoretical elements with considerations about fieldwork carried out using the dialectical method.